2014
DOI: 10.1080/02640414.2014.926384
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between running economy and running performance in elite Kenyan distance runners

Abstract: The purpose of this study was to investigate the relationship between running economy (RE) and performance in a homogenous group of competitive Kenyan distance runners. Maximal aerobic capacity (VO2max) (68.8 ± 3.8 ml∙kg(-1)∙min(-1)) was determined on a motorised treadmill in 32 Kenyan (25.3 ± 5.0 years; IAAF performance score: 993 ± 77 p) distance runners. Leg anthropometry was assessed and moment arm of the Achilles tendon determined. While Achilles moment arm was associated with better RE (r(2) = 0.30, P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 46 publications
11
46
0
1
Order By: Relevance
“…Whilst we agree with the multi-factorial hypothesis for Kenyan running success, as acknowledged by Mooses et al (2014) and argued elsewhere (Larsen, 2003;Tucker, Santos-Concejero, & Collins, 2013;Wilber & Pitsiladis, 2012), we do not believe that RE can be overlooked or even downplayed to the extent that it was based on this particular study. Previous research in African runners in general (Weston, Mbambo, & Myburgh, 2000), and East African runners in particular (Lucia et al, 2006;Saltin et al, 1995) has shown that African runners are more metabolically economical than elite European runners.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…Whilst we agree with the multi-factorial hypothesis for Kenyan running success, as acknowledged by Mooses et al (2014) and argued elsewhere (Larsen, 2003;Tucker, Santos-Concejero, & Collins, 2013;Wilber & Pitsiladis, 2012), we do not believe that RE can be overlooked or even downplayed to the extent that it was based on this particular study. Previous research in African runners in general (Weston, Mbambo, & Myburgh, 2000), and East African runners in particular (Lucia et al, 2006;Saltin et al, 1995) has shown that African runners are more metabolically economical than elite European runners.…”
supporting
confidence: 81%
“…Mooses and colleagues recently argued that since they found no association between running economy (RE) and running performance in elite Kenyan distance runners, a superior RE per se could not account for the superior performance of the East African runners, and that RE is compensated for by other factors to enable superior distance running performance (Mooses et al, 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It appears that modifications to this lever arm, sometimes referred to as a gearing ratio [79], can place the athlete in a more optimal position for increasing performance. Related research on running has shown that the relationship or the ratio of the lever arm from the Achilles tendon to the ankle joint, and the point of application from the ground reaction force underneath the ball of the foot to the ankle joint, can have an influence on running economy [80,81].…”
Section: Musculoskeletal Propertiesmentioning
confidence: 99%